Strengthening the Innovation Capacity of Student PKM Proposals through an AI-Generative-Based Co-Creation Learning Model with a Classroom Action Research Approach - Nurrahmah Agusnaya; Putri Nirmala; M. Miftach Fakhri; Wahyu Hidayat M; Rosidah Rosidah (PT. Global Research Collaboration, 2025)
The low quality of student innovation in preparing Student Creativity Program (PKM) proposals remains a challenge in higher education, caused by limited research experience, weak team collaboration, and low utilization of Artificial Intelligence (AI) technology. This study aims to describe the implementation of an AI-based Co-Creation Learning model in improving students' abilities to prepare PKM proposals. This research used the Classroom Action Research (CAR) method, which was conducted in two cycles: the first cycle applied the Project-Based Learning (PjBL) model, and the second cycle applied the AI- based Co-Creation Learning model. The results showed an increase in the students’ average scores from 86.1 in the first cycle to 88.4 in the second cycle, with a decrease in the standard deviation from 2.32 to 1.37. Inferential analysis using a paired samples t-test revealed a t-value of -9.25 with p < 0.001 and an effect size (Cohen’s d) of -1.46, indicating a statistically significant improvement in learning outcomes. This model effectively supports collaboration, creativity, and students' skills in developing more relevant PKM proposals. Thus, the implementation of the AI-based Co-Creation Learning model is effective in enhancing students’ innovation capacity and supports the Merdeka Belajar Kampus Merdeka policy in strengthening excellent human resources in the digital era.